Consistency assessment of a canine heartworm point-of-care antigen test using fresh whole blood and archived sera - Andrew Falkiner; Jacinta Finlayson; Charles Caraguel; Peter J. Atkinson (Veterinary Parasitology, 2026)

Zero tillage impacts on soil physical properties but not on crop yield - Sajjad Raza; Brian S. Atkinson; Imrul Hossain; Ho-Chul Shin; Hannah V. Cooper; Craig J. Sturrock; Andrew B. Riche; Malcolm J. Hawkesford; Sacha J. Mooney (European Journal of Agronomy, 2026)

Contemporary Methods for Capturing Juvenile Salmonids in the Marine Environment - Sean C. Godwin; Emma M. Atkinson; Jamieson B. Atkinson; Mackenzie C. Bartlett; William D. P. Duguid; Marc Trudel; Andrew W. Bateman (Fish and Fisheries, 2026)
Anadromous salmonids play vital roles in marine and freshwater ecosystems. The most abundant of these fishes—Pacific salmon ( Oncorhynchus spp.)—are integral to coastal ecosystems and communities across the North Pacific Rim, but numerous populations are experiencing dramatic declines, particularly towards the south of their range. Although many declines have been linked to poor marine survival, the early marine life phase of salmon has historically been difficult to study because of challenges in capturing juvenile salmon once they leave freshwater. Recent advancements in capture methods, refined over decades of research, have greatly expanded our understanding of juvenile Pacific salmon life history. Here, we synthesise and review the literature on the five main capture techniques for juvenile Pacific salmon in the marine environment: beach seine, miniature purse seine, conventional purse seine, microtroll, and rope trawl. We compare gear, selectivity, cost, and fish welfare considerations across methods. Along with demonstrated utility in Pacific salmon research, these methods also have broad—and in some cases unexplored—applicability for studying other salmonids and nearshore marine fishes globally, including invasive populations and Atlantic salmon.

Locomotion Reveals Contrasting Responses in Body Mass‐Scaling of Metabolic Rates Between Winged and Wingless Arthropods - Vojsava Gjoni; Hanrong Tan; Andrew G. Hirst; Pavel Kratina; David Atkinson (Ecology Letters, 2025)
Metabolism fuels fundamental biological processes and commonly scales with body mass with an exponent, b , between 2/3 and 1. We, here, explore how differences in physical activity can reveal contrasting interspecific metabolic scaling between major groups of arthropods. The Metabolic‐level Boundaries Hypothesis predicts that increased behavioural activity increases b . We test this hypothesis by comparing b during flight, non‐flight locomotion, and rest in winged and wingless insects, and spiders. We find that interspecific b values increase with activity only with flight in winged insects which co‐occurs with a substantial flight‐related rise in metabolic level. Spiders show a shallower interspecific metabolic scaling relative to insects, potentially reflecting slower life‐history strategies with increasing body size. Consequently, large resting or walking insects consume 6–15 times more oxygen than do spiders of corresponding size and activity level. These fundamental differences offer new insights into the evolutionary dynamics of arthropod energetics.

Pace of alcohol drinking during in natural-environment drinking is associated with heightened alcohol-related reward and negative consequences in risky drinkers - Emily A. Atkinson; Andrew M. Fischer; John F. Cursio; Andrea C. King; Daniel J. Fridberg (Psychopharmacology, 2025)

The winds of change? Attitudes toward wind projects and their electoral implications in Texas - Talbot M. Andrews; Carol Atkinson-Palombo; Oksan Bayulgen; Adam Gallaher; Lyle Scruggs (Energy Policy, 2025)

Mechanistic safety assessment via multi-omic characterisation of systemic pathway perturbations following in vivo MAT2A inhibition - Valentina Fogal; Filippos Michopoulos; Andrew F. Jarnuczak; Ghaith M. Hamza; Stephanie Harlfinger; Paul Davey; Heather Hulme; Stephen J. Atkinson; Piotr Gabrowski; Tony Cheung; Michael Grondine; Clare Hoover; et al. (Archives of Toxicology, 2024)
The tumour suppressor p16/CDKN2A and the metabolic gene, methyl-thio-adenosine phosphorylase (MTAP), are frequently co-deleted in some of the most aggressive and currently untreatable cancers. Cells with MTAP deletion are vulnerable to inhibition of the metabolic enzyme, methionine-adenosyl transferase 2A (MAT2A), and the protein arginine methyl transferase (PRMT5). This synthetic lethality has paved the way for the rapid development of drugs targeting the MAT2A/PRMT5 axis. MAT2A and its liver- and pancreas-specific isoform, MAT1A, generate the universal methyl donor S-adenosylmethionine (SAM) from ATP and methionine. Given the pleiotropic role SAM plays in methylation of diverse substrates, characterising the extent of SAM depletion and downstream perturbations following MAT2A/MAT1A inhibition (MATi) is critical for safety assessment. We have assessed in vivo target engagement and the resultant systemic phenotype using multi-omic tools to characterise response to a MAT2A inhibitor (AZ’9567). We observed significant SAM depletion and extensive methionine accumulation in the plasma, liver, brain and heart of treated rats, providing the first assessment of both global SAM depletion and evidence of hepatic MAT1A target engagement. An integrative analysis of multi-omic data from liver tissue identified broad perturbations in pathways covering one-carbon metabolism, trans-sulfuration and lipid metabolism. We infer that these pathway-wide perturbations represent adaptive responses to SAM depletion and confer a risk of oxidative stress, hepatic steatosis and an associated disturbance in plasma and cellular lipid homeostasis. The alterations also explain the dramatic increase in plasma and tissue methionine, which could be used as a safety and PD biomarker going forward to the clinic.

Determinants of host breadth in non-native bark and ambrosia beetles - Soňa Šenfeldová; Thomas H. Atkinson; Miloš Knížek; Robert J. Rabaglia; Nathan P. Havill; Samuel F. Ward; Marek Turčáni; Andrew M. Liebhold (Forest Ecology and Management, 2024)

Long‐term shifts in phenology, thermal niche, population size, and their interactions in marine pelagic copepods - Stefano Corona; Andrew G. Hirst; David Atkinson; Jasmin Renz; Maarten Boersma; Angus Atkinson (Limnology and Oceanography, 2024)
Under climatic warming many species shift their seasonal timing of life cycle events (phenology) and seasonal abundance distribution, but whether they maintain the same thermal niche is still poorly understood. Here, we studied multidecadal trends in abundance and phenology of seven major copepod species across three stations (Stonehaven (SH), Helgoland Roads (HR), and Plymouth L4) on the North–West European shelf, spanning ~ 6.5° of latitude. All seven species consistently occupied colder temperatures at the northern station compared to the southerly station, but they maintained the same realized thermal niche over years. Expected phenological shifts (i.e., earlier when warmer) in some stations were obscured possibly by the long‐term drop of copepod density in spring–summer, which may be due to a variation in the food/predators abundance. The ongoing spring–summer declines in abundance (~ 50%) of many North Atlantic pelagic species over the last five decades, as found in recent studies, may have also influenced the metrics of seasonal timing. To separate the seasonal timing of life events from that of seasonal abundance distribution, we used a time series of egg production rate (EPR) of Calanus helgolandicus at L4, and found that this shifted later into the summer–autumn over the last 30 yr of warming, coincident with declining spring–summer food and increasing predator abundance. Overall, direct temperature effects do appear to influence the seasonal timing of the copepods, but to explain impacts at individual stations or long‐term trends in population size or phenology, understanding the changing balance of food and predators appears to be critical.

Unconfined fishway design, implementation, and assessment for the emerald Shiner (Notropis atherinoides) in the Upper Niagara River, New York - Jundong Qiao; Sean J. Bennett; Joseph F. Atkinson; Paul A. Cocca; Sarah K. Delavan; Andrew R. Hannes; Bryan A. Hinterberger; Timothy J. Pede; Alicia Pérez-Fuentetaja; Richard J. Ruby (Ecological Engineering, 2024)

Responses of intraspecific metabolic scaling to temperature and activity differ between water‐ and air‐breathing ectothermic vertebrates - Guillermo García‐Gómez; Andrew G. Hirst; Matthew Spencer; David Atkinson (Ecology Letters, 2024)
Metabolism underpins all life‐sustaining processes and varies profoundly with body size, temperature and locomotor activity. A current theory explains some of the size‐dependence of metabolic rate (its mass exponent, b ) through changes in metabolic level ( L ). We propose two predictive advances that: (a) combine the above theory with the evolved avoidance of oxygen limitation in water‐breathers experiencing warming, and (b) quantify the overall magnitude of combined temperatures and degrees of locomotion on metabolic scaling across air‐ and water‐breathers. We use intraspecific metabolic scaling responses to temperature (523 regressions) and activity (281 regressions) in diverse ectothermic vertebrates (fish, reptiles and amphibians) to show that b decreases with temperature‐increased L in water‐breathers, supporting surface area‐related avoidance of oxygen limitation, whereas b increases with activity‐increased L in air‐breathers, following volume‐related influences. This new theoretical integration quantitatively incorporates different influences (warming, locomotion) and respiration modes (aquatic, terrestrial) on animal energetics.

Soil structure has a greater effect on the rooting of wheat (Triticum aestivum L.) than nitrogen fertilisation rate or genotype - Tinashe Mawodza; Hu Zhou; Brian S. Atkinson; Jonathan A. Atkinson; Craig J. Sturrock; Andrew B. Riche; W. Richard Whalley; Malcolm J. Hawkesford; Hannah V. Cooper; Sacha J. Mooney (Rhizosphere, 2023)

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

Rare germline variants in the AXIN2 gene in families with colonic polyposis and colorectal cancer - James M. Chan; Mark Clendenning; Sharelle Joseland; Peter Georgeson; Khalid Mahmood; Romy Walker; Julia Como; Jihoon E. Joo; Susan Preston; Ryan A. Hutchinson; Bernard J. Pope; Andrew Metz; et al. (Familial Cancer, 2022)

Density‐dependent modulation of copepod body size and temperature–size responses in a shelf sea - Stefano Corona; Andrew Hirst; David Atkinson; Angus Atkinson (Limnology and Oceanography, 2021)
Body size is a fundamental trait in ecology, and body size reduction with increasing temperature has been termed the third universal response to climate warming. Although effects of temperature and food on phenotypic plasticity of zooplankton adult body size have been investigated, density‐dependent effects have been neglected. We measured seasonal changes in the prosome length of 7098 adult females of 7 dominant copepod species in 13 yr spanning a 27‐yr period of warming at the L4 time series off Plymouth, UK. The seasonal temperature–size (T–S) response varied greatly among species, from reductions of 2.93% of carbon mass °C −1 for Paracalanus parvus to 10.15% of carbon mass °C −1 for Temora longicornis . Evidence for a long‐term T–S response was detected in at least two species, supporting the hypothesis that climatic warming leads to smaller adult sizes. April was a crucial month for determining the strength of the T–S response. During this month, body size related negatively to total zooplankton abundance. We suggest that the mechanism for this density dependence is via competition for food and/or intraguild predation, since spring was also the period when the ratio of food biomass to zooplankton biomass was at its lowest. Our study is among the first in situ demonstrations of density‐dependent effects on the body size of marine zooplankton and shows the need to consider the effect of top‐down as well as bottom‐up factors on body size in a warming climate.

Characteristics of respiratory virus infections in autologous hematopoietic stem cell transplantation patients, a prospective study, Bern, Switzerland, 2015–2017 - Fabienne Moret; Jonas Marschall; Andrew Atkinson; Sarah Farag; Stefan Zimmerli; Thomas Pabst; Rami Sommerstein (Infectious Diseases, 2021)

Chronically elevated depressive symptoms interact with acute increases in inflammation to predict worse neurocognition among people with HIV - Rowan Saloner; Emily W. Paolillo; Robert K. Heaton; David J. Grelotti; Murray B. Stein; Andrew H. Miller; J. Hampton Atkinson; Scott L. Letendre; Ronald J. Ellis; Igor Grant; Jennifer E. Iudicello; David J. Moore (Journal of NeuroVirology, 2021)

Increasing nutrient stress reduces the efficiency of energy transfer through planktonic size spectra - Angus Atkinson; Martin K.S. Lilley; Andrew G. Hirst; Andrea J. McEvoy; Glen A. Tarran; Claire Widdicombe; Elaine S. Fileman; E. Malcolm S. Woodward; Katrin Schmidt; Tim J. Smyth; Paul J. Somerfield (Limnology and Oceanography, 2021)
Size‐spectral approaches quantify the efficiency of energy transfer through food webs, but theory and field studies disagree over how changes in temperature, nutrients, and extreme weather impact on this efficiency. We address this at two scales: via 6 years of weekly sampling of the plankton size spectrum at the Plymouth L4 shelf sea site, and via a new, global‐scale, meta‐analysis of aquatic size spectra. The time series showed that with summertime nutrient starvation, the energy transfer efficiency from picoplankton to macroplankton decreased (i.e., steepening slopes of the size spectra). This reflected increasing dominance by small cells and their microbial consumers. The extreme storms in winter 2013/2014 caused high metazoan mortality, steep size‐spectral slopes, and reduced plankton biomass. However, recovery was within months, demonstrating an inbuilt resilience of the system. Both L4 and our meta‐analysis showed steep slopes of normalized size spectra (median −1.11). This reflects much lower values, either of trophic transfer efficiency (3.5%) or predator–prey mass ratio (569), compared to commonly quoted values. Results from the meta‐analysis further showed that to represent energy transfer faithfully, size spectra are best constructed in units of carbon mass and not biovolume, and span a mass range of > 10 7 . When this range is covered, both the meta‐analysis and time series show a dome‐shaped relationship between spectral slopes and plankton biomass, with steepening slopes under increasingly oligotrophic and eutrophic conditions. This suggests that ocean warming could decrease the efficiency of energy transfer through pelagic food webs via indirect effects of increasing stratification and nutrient starvation.

Navigating Institutional Challenges: Design to Enable Community Participation in Social Learning for Freshwater Planning - James A. Turner; Will Allen; Caroline Fraser; Andrew Fenemor; Akiko Horita; Toni White; Lan Chen; Maggie Atkinson; Michelle Rush (Environmental Management, 2020)

Resilience of the Copepod Oithona similis to Climatic Variability: Egg Production, Mortality, and Vertical Habitat Partitioning - Louise Elisabeth Cornwell; Elaine S. Fileman; John T. Bruun; Andrew Garwood Hirst; Glen Adam Tarran; Helen S. Findlay; Ceri Lewis; Timothy James Smyth; A. J. McEvoy; A. Atkinson (Frontiers in Marine Science, 2020)

Dose evaluation of intravenous metamizole (dipyrone) in infants and children: a prospective population pharmacokinetic study - Victoria C. Ziesenitz; Frédérique Rodieux; Andrew Atkinson; Carole Borter; Julia A. Bielicki; Manuel Haschke; Urs Duthaler; Fabio Bachmann; Thomas O. Erb; Nicolas Gürtler; Stefan Holland-Cunz; Johannes N. van den Anker; et al. (European Journal of Clinical Pharmacology, 2019)

A synthesis of major environmental-body size clines of the sexes within arthropod species - Curtis R. Horne; Andrew G. Hirst; David Atkinson (Oecologia, 2019)

Oust the louse: leaping behaviour removes sea lice from wild juvenile sockeye salmon Oncorhynchus nerka - Emma M. Atkinson; Andrew W. Bateman; Lawrence M. Dill; Martin Krkošek; John D. Reynolds; Sean C. Godwin (Journal of Fish Biology, 2018)
We conducted a manipulative field experiment to determine whether the leaping behaviour of wild juvenile sockeye salmon Oncorhynchus nerka dislodges ectoparasitic sea lice Caligus clemensi and Lepeophtheirus salmonis by comparing sea‐lice abundances between O. nerka juveniles prevented from leaping and juveniles allowed to leap at a natural frequency. Juvenile O. nerka allowed to leap had consistently fewer sea lice after the experiment than fish that were prevented from leaping. Combined with past research, these results imply potential costs due to parasitism and indicate that the leaping behaviour of juvenile O. nerka does, in fact, dislodge sea lice.

Mortality of Calanus helgolandicus : Sources, differences between the sexes and consumptive and nonconsumptive processes - Jacqueline L. Maud; Andrew G. Hirst; Angus Atkinson; Penelope K. Lindeque; Andrea J. McEvoy (Limnology and Oceanography, 2018)
While losses from mortality are as important as gains from reproduction in zooplankton population dynamics, the former are more challenging to quantify. We used two approaches to provide complementary insights into the mortality of a biomass‐dominant copepod, Calanus helgolandicus , at Station L4 in the English Channel. Using a neutral‐red staining method, we found that dead carcasses represented a mean of 9% of the C. helgolandicus copepodites sampled. The resulting nonconsumptive mortality rates are the first that have been derived for C. helgolandicus ; and estimates suggest a contribution of 0–54% (median of 4.4%) to the total mortality rate. Consumptive mortality (i.e., that due to removal by predation), dominated for most of the year and contributed a mean of 89% to total mortality. Nonconsumptive mortality increased during summer and winter, and was positively related to maximum wind speed during the preceding 72 h, indicating that extreme weather events may lead to increased mortality. Using the Vertical Life Table approach, mortality rates across the CV‐adult male stage pair were on average ∼ 2.5 times greater than those of CV‐adult females. Adult male consumptive mortality rates were ∼ 6 times greater than those for females; adult male nonconsumptive rates were twice those of females, suggesting that predation is of greater significance to male loss rates. Summer CV‐adult mortality rates were positively correlated to temperature, and to the abundance of predatory chaetognaths and siphonophores, suggesting that the gelatinous predator assemblage is the dominant agent for population control of late stage copepodites of C. helgolandicus at L4.

Climate change is predicted to alter the current pest status of Globodera pallida and G. rostochiensis in the United Kingdom - Laura M. Jones; Ann‐Kristin Koehler; Mirek Trnka; Jan Balek; Andrew J. Challinor; Howard J. Atkinson; Peter E. Urwin (Global Change Biology, 2017)
The potato cyst nematodes Globodera pallida and G. rostochiensis are economically important plant pathogens causing losses to UK potato harvests estimated at £50 m/ year. Implications of climate change on their future pest status have not been fully considered. Here, we report growth of female G. pallida and G. rostochiensis over the range 15 to 25°C. Females per plant and their fecundity declined progressively with temperatures above 17.5°C for G. pallida , whilst females per plant were optimal between 17.5 and 22.5°C for G. rostochiensis . Relative reproductive success with temperature was confirmed on two potato cultivars infected with either species at 15, 22.5 and 25°C. The reduced reproductive success of G. pallida at 22.5°C relative to 15°C was also recorded for a further seven host cultivars studied. The differences in optimal temperatures for reproductive success may relate to known differences in the altitude of their regions of origin in the Andes. Exposure of G. pallida to a diurnal temperature stress for one week during female growth significantly suppressed subsequent growth for one week at 17.5°C but had no effect on G. rostochiensis . However, after two weeks of recovery, female size was not significantly different from that for the control treatment. Future soil temperatures were simulated for medium‐ and high‐emission scenarios and combined with nematode growth data to project future implications of climate change for the two species. Increased soil temperatures associated with climate change may reduce the pest status of G. pallida but benefit G. rostochiensis especially in the southern United Kingdom. We conclude that plant breeders may be able to exploit the thermal limits of G. pallida by developing potato cultivars able to grow under future warm summer conditions. Existing widely deployed resistance to G. rostochiensis is an important characteristic to retain for new potato cultivars.

A global synthesis of seasonal temperature–size responses in copepods - Curtis R. Horne; Andrew G. Hirst; David Atkinson; Aitana Neves; Thomas Kiørboe (Global Ecology and Biogeography, 2016)
Aim Body size is a master trait with significant ecological importance. Seasonal changes in body size within diverse ectothermic species can result from different environmental conditions experienced during ontogeny in subsequent generations. Whilst intraspecific changes in adult size have been well studied under controlled experimental conditions and across geographical ranges, comprehensive analyses of temporal changes are lacking, and there remains considerable unexplained variation in body size responses within aquatic taxa. Using planktonic copepods as an exemplar taxon, we quantify variation in adult body mass within seasonally varying marine and freshwater environments. We describe how size variation relates to temperature, food concentration (chlorophyll‐ a ) and life‐history characteristics, including feeding strategy. Location Global. Methods Using a meta‐analytic approach we extract quantitative data from published literature on seasonal size responses of copepods. We analyse competing models to determine the best predictors of these responses, and compare the relative importance of temperature and chlorophyll‐ a concentration in explaining variation in body size. Results We quantify 140 seasonal size responses from 33 different global locations, representing 48 planktonic copepod species from four taxonomic orders. We find that temperature ( r 2 = 0.50), rather than food ( r 2 = 0.22), is the dominant explanatory variable of changes in adult body size across seasons. A striking outcome is that calanoid copepods, which utilize feeding currents to capture prey, exhibit a four‐fold greater reduction in adult body mass per °C (−3.66%) compared with cyclopoid copepods (−0.91%), which are ambush feeders. By contrast, species body size or reproductive strategy did not explain variation in the seasonal temperature–size response. Main conclusions Our findings lead us to suggest that feeding strategies may play a significant role in dictating the magnitude of seasonal temperature–size responses in copepods, with potential implications for other ectotherms with diverse feeding methods. Seasonal temperature–size responses were typically much more variable than responses in laboratory studies that provided excess food, suggesting that field conditions modify the temperature–size response.

Seasonal nutritional status in Norway lobsters, Nephrops norvegicus (L.): are females nutritionally compromised over the winter? - Andrew J. R. Watts; Amaya Albalat; Ian P. Smith; Robert J. A. Atkinson; Douglas M. Neil (Marine Biology Research, 2016)

NiftyFit: a Software Package for Multi-parametric Model-Fitting of 4D Magnetic Resonance Imaging Data - Andrew Melbourne; Nicolas Toussaint; David Owen; Ivor Simpson; Thanasis Anthopoulos; Enrico De Vita; David Atkinson; Sebastien Ourselin (Neuroinformatics, 2016)

Temperature‐size responses match latitudinal‐size clines in arthropods, revealing critical differences between aquatic and terrestrial species - Curtis R. Horne; Andrew. G. Hirst; David Atkinson (Ecology Letters, 2015)
Two major intraspecific patterns of adult size variation are plastic temperature‐size (T‐S) responses and latitude‐size (L‐S) clines. Yet, the degree to which these co‐vary and share explanatory mechanisms has not been systematically evaluated. We present the largest quantitative comparison of these gradients to date, and find that their direction and magnitude co‐vary among 12 arthropod orders ( r 2 = 0.72). Body size in aquatic species generally reduces with both warming and decreasing latitude, whereas terrestrial species have much reduced and even opposite gradients. These patterns support the prediction that oxygen limitation is a major controlling factor in water, but not in air. Furthermore, voltinism explains much of the variation in T‐S and L‐S patterns in terrestrial but not aquatic species. While body size decreases with warming and with decreasing latitude in multivoltine terrestrial arthropods, size increases on average in univoltine species, consistent with predictions from size vs. season‐length trade‐offs.

From animal cage to aircraft cabin: an overview of evidence translation in jet lag research - Greg Atkinson; Alan M. Batterham; Nigel Dowdall; Andrew Thompson; Alwin van Drongelen (European Journal of Applied Physiology, 2014)

Three-dimensional hydrofacies assemblages in ice-contact/proximal sediments forming a heterogeneous ‘hybrid’ hydrostratigraphic unit in central Illinois, USA - Lisa A. Atkinson; Martin Ross; Andrew J. Stumpf (Hydrogeology Journal, 2014)

Body shape shifting during growth permits tests that distinguish between competing geometric theories of metabolic scaling - Andrew G. Hirst; Douglas S. Glazier; David Atkinson (Ecology Letters, 2014)
Metabolism fuels all of life's activities, from biochemical reactions to ecological interactions. According to two intensely debated theories, body size affects metabolism via geometrical influences on the transport of resources and wastes. However, these theories differ crucially in whether the size dependence of metabolism is derived from material transport across external surfaces, or through internal resource‐transport networks. We show that when body shape changes during growth, these models make opposing predictions. These models are tested using pelagic invertebrates, because these animals exhibit highly variable intraspecific scaling relationships for metabolic rate and body shape. Metabolic scaling slopes of diverse integument‐breathing species were significantly positively correlated with degree of body flattening or elongation during ontogeny, as expected from surface area theory, but contradicting the negative correlations predicted by resource‐transport network models. This finding explains strong deviations from predictions of widely adopted theory, and underpins a new explanation for mass‐invariant metabolic scaling during ontogeny in animals and plants.

Effects of dawn simulation on markers of sleep inertia and post-waking performance in humans - Andrew Thompson; Helen Jones; Warren Gregson; Greg Atkinson (European Journal of Applied Physiology, 2014)

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

Effects of alcohol preload on attentional bias towards cocaine-related cues - Catharine Montgomery; Matt Field; Amanda M. Atkinson; Jon C. Cole; Andrew J. Goudie; Harry R. Sumnall (Psychopharmacology, 2010)

Micronutrient deficiencies in maternity and child health: a review of environmental and social context and implications for Malawi - Natalie Dickinson; Gordon Macpherson; Andrew S. Hursthouse; John Atkinson (Environmental Geochemistry and Health, 2009)

Unusual new Chaetosphaeria species from New Zealand: Intrafamilial diversity and elucidations of the Chaetosphaeriaceae ‐Lasiosphaeriaceae relationship (Sordariomycetes, Ascomycotina) - Toni J. Atkinson; Andrew N. Miller; Sabine M. Huhndorf; David A. Orlovich (New Zealand Journal of Botany, 2007)
Chaetosphaeria albida, C. bombycina , and C. metallicans are described and compared with other Chaetosphaeria taxa using morphological and molecular methods. The fresh ascomata of C. albida are almost white, translucent, and aereolate; they are papillate with a distinctive 4‐layered peridium, and the ascospores are scolecosporous, multiseptate, and hyaline. C. bombycina is similar, but the fresh ascomata are light fawn‐grey with a reflective silken appearance, non‐papillate, and the similar peridium is 3‐layered. C. metallicans has ascomata which are blue‐black, shiny and metallic when fresh; the thick peridium is heavily melanised, and the ascospores are straight to allantoid, 3‐septate, and hyaline. The scolecosporous ascospores of C. albida and C. bombycina would have traditionally referred these taxa to Lasiosphaeria . However, like C. metallicans , they lack a peridial tomentum, and have asci with light‐refractive, non‐amyloid apical rings, without a sub‐apical globule. Despite the major differences in spore shape and ascomal wall structure, analyses of the LSU and ITS regions of ribosomal DNA suggest that genetically all three fall within Chaetosphaeria , near to C. raciborskii , and in a sister clade to the type species C. innumera . The placement of these species considerably expands current morphological conceptions of Chaetosphaeria , particularly in terms of ascomal wall appearance and structure, and confirms the existence of a scolecosporous group within the genus. in the search for morphological characters which mimic genetic relationships, this study further elucidates the relationship between the Chaetosphaeriaceae and the Lasiosphaeriaceae.

Transformation of Actinidia eriantha: A potential species for functional genomics studies in Actinidia - Tianchi Wang; Yidong Ran; Ross G. Atkinson; Andrew P. Gleave; Dan Cohen (Plant Cell Reports, 2006)

Porosity Imaging in Porous Media Using Synchrotron Tomographic Techniques - Mark Betson; John Barker; Paul Barnes; Tim Atkinson; Andrew Jupe (Transport in Porous Media, 2004)

Growth rates of Antarctic krill, Euphausia superba: Comparison of the instantaneous growth rate method with nitrogen and phosphorus stoichiometry - Katharine H. Arnold; Rachael S. Shreeve; Angus Atkinson; Andrew Clarke (Limnology and Oceanography, 2004)
Zooplankton growth rates are hard to measure directly, and proxy measurements are desirable to encompass the variety of species and scales of interest. The growth rate hypothesis of stoichiometric theory states that a negative relationship exists between nitrogen : phosphorus (N : P) stoichiometry and growth rate, driven by cellular ribosomal ribonucleic acid (rRNA) content. Despite the wealth of literature on the growth rate hypothesis, there exist no practical demonstrations of its use in the marine literature. We thus investigated whether this hypothesis could be the basis of a technique to estimate growth rates of Euphausia superba by comparing, for the same individual krill, elemental stoichiometry and growth rates derived from the instantaneous growth rate (IGR) method. These growth rates were the first IGR measurements from South Georgia; from within a restricted area over the course of just 1 month, these rates were highly variable, from negative to near maximum rates recorded for the species. Although there were significant differences in N: P ratio and phosphorus content between individuals and schools, there was no relationship between N: P ratio and growth rate when data were grouped by school. Thus, our data do not support the predictions of the growth rate hypothesis at an intraspecific scale. However, when all data were pooled, the mean values of growth rate and N: P ratio did fit the interspecific relationship established previously for freshwater zooplankton. We suggest that krill maintain the biochemical machinery for high growth potential and maintain high growth in summer to take advantage of short‐term fluctuations in food.

Evaluation of the Best disease gene in patients with age-related macular degeneration and other maculopathies - R. Allikmets; Johanna M. Seddon; Paul S. Bernstein; A. Hutchinson; Andrew Atkinson; Sanjay Sharma; Bernard Gerrard; W. Li; Michael L. Metzker; Claes Wadelius; C. Thomas Caskey; Michael Dean; et al. (Human Genetics, 1999)